Uso de enmiendas para reducir la salinidad en suelos agrícolas y su impacto en los cultivos del cantón Milagro - Yanez Rivas, Fernando Jose (2025)
This work investigates how amendments can decrease salinity in agricultural soils and their effect on crop productivity. Soil is an indispensable resource for human beings, since it is the main carrier of food. However, it is affected by several factors, including salinity, which impairs the soil's capacity to retain water and nutrients, reducing crop yields. The main objective of this study is to analyze how amendments can help reduce soil salinity and its effect on agricultural production. It also seeks to identify the main causes of salinity, evaluate different types of amendments and determine which are most effective. To achieve this, research has been carried out based on the analysis of scientific literature and specialized documents without conducting new experiments. The results show that salinity can be caused by both natural factors and inappropriate agricultural practices. Organic amendments, such as compost or manure, were found to significantly improve soil structure and its ability to retain water. On the other hand, chemical amendments such as gypsum or magnesium sulfate help reduce sodium levels and improve soil fertility. In conclusion, applying these amendments along with smart irrigation management and salt-resistant crops is crucial to reduce soil salinity. It is important to educate farmers about sustainable practices to protect our soil and gradually increase our long-term agricultural productivity